India's platform economy and emerging regulatory challenges - Rajat Kathuria; Mansi Kedia; Kaushambi Bagchi (Indian Council for Research on International Economic Relations (ICRIER), 2021)
The phenomenal rise of the platform economy has reshaped how economies operate across the world. The importance of digital platforms has never been more evident than in combatting the ongoing corona virus (Covid-19) pandemic. Even with the threat of a global recession looming large, technology companies are witnessing a surge in demand for their services. Platforms distinguish themselves from traditional markets by demonstrating speed and scale of innovation and fostering efficient and productive interaction between buyers and sellers. Enterprises using platform-based business models have expanded beyond social media, travel and entertainment to sectors like financial services, healthcare, logistics and transportation. With the objective of building evidence for policy-making in this sector, this study undertakes an in-depth analysis of the impact generated by the platform economy in India, by estimating consumer surplus from the use of platforms, analysing its impact on traditional businesses either by transformation or disruption. The estimated consumer surplus is Rs. 438.75 per individual per month, amounting to a collective annual surplus of Rs. 3620 billion for India. At current exchange rates this would amount to USD 47 billion. The growth of platforms has also been accompanied by global concern against their anticompetitive practices, the spread of fake news and harmful content, political bias, etc. The paper discusses regulatory changes and areas of concern for market competition, labour and employment, fake news and misinformation, consumer protection, counterfeit goods and data privacy in India.
Keywords: L22; L38; L44; 330; Platform Economy; Consumer Surplus; Regulation; Disruption